Evaluation Use in Evaluation Systems: The Case of the European Commission - Steven Højlund (Copenhagen Business School (CBS), 2015)
What effect do evaluation systems have on the use of evaluation? This is the research question guiding this PhD thesis. By answering this research question as well as three sub-questions, the thesis addresses three important gaps in the evaluation literature: the first gap is that evaluation theory does a poor job explaining non-use and justificatory uses of evaluation. The second gap is that evaluation theory does not account for the systemic context of evaluation in its more general explanations of evaluation use. Finally, the literature does not account empirically for the micro-level of evaluation use in evaluation systems. The thesis draws inspiration from organisational theory and in particular organisational institutionalism. Organisational institutionalism explains organisational action and change to be driven by legitimacy-seeking organisational behaviour. Organisations seek to legitimise themselves in order to survive in their environment. This theory is applied to the concept `evaluation system'. Hence, the assumption underlying this thesis is that organisations within an evaluation system are using evaluations to appear accountable rather than improve policies. The thesis investigates the European Union's evaluation system with a particular focus on the European Commission. This is done in four articles. The first article is a theoretical article introducing organisational institutionalism to the evaluation literature in order to explain non-use and justificatory uses of evaluations. The second article is a historical analysis of the development of the European Commissions evaluation practices. The third article is a case-based analysis of evaluation use in the European Commission. The fourth article is also an empirical article on policy learning from evaluations in three different Directorate-Generals in the European Commission. The methodology used in the empirical articles is qualitative content analysis and the data were more than a hundred Commission documents and 58 interviews with Commission staff.
hdl:10398/9117
Keywords: 650